(untitled) (Proceedings of International Educators Conference, 2024)
The energy lost in the control circuit turns into heat, increasing the temperature of the working fluid, which reduces its viscosity, increases the flow of leakage, and in turn is accompanied by a progressive increase in temperature due to the additional loss of escape energy.